4D Printing of Humidity‐Driven Seed Inspired Soft Robots. Issue 9 (1st February 2023) - Cecchini, Luca; Mariani, Stefano; Ronzan, Marilena; Mondini, Alessio; Pugno, Nicola M.; Mazzolai, Barbara
Abstract: Geraniaceae seeds represent a role model in soft robotics thanks to their ability to move autonomously across and into the soil driven by humidity changes. The secret behind their mobility and adaptivity is embodied in the hierarchical structures and anatomical features of the biological hygroscopic tissues, geometrically designed to be selectively responsive to environmental humidity. Following a bioinspired approach, the internal structure and biomechanics of Pelargonium appendiculatum (L.f.) Willd seeds are investigated to develop a model for the design of a soft robot. The authors exploit the re‐shaping ability of 4D printed materials to fabricate a seed‐like soft robot, according to the natural specifications and model, and using biodegradable and hygroscopic polymers. The robot mimics the movement and performances of the natural seed, reaching a torque value of ≈30 µN m, an extensional force of ≈2.5 mN and it is capable to lift ≈100 times its own weight. Driven by environmental humidity changes, the artificial seed is able to explore a sample soil, adapting its morphology to interact with soil roughness and cracks. Abstract : The internal structure and biomechanics of Pelargonium appendiculatum (L.f.) wild seeds are investigated to develop a model for the design and 4D printing of a soft robot. The robot mimics the movement and performances of the natural seed. Driven by environmental humidity, the artificial seed can explore a sample soil, adapting its morphology to interact with soil roughness and cracks.